Heart rate variability in biophilic design: A systematic literature review - Vidyarini, Etika; Riyadi, Slamet; Pasaribu, Yannes Martinus (Institut Seni Indonesia Yogyakarta, 2024)
The use of Virtual Reality as a representation of biophilic design has been commonly used for design evaluations on human perception and performance before the actual construction. Biophilic design is known for the relaxing effects on human physiological responses; particularly cardiac activity indexed by Heart Rate Variability (HRV), representing human’s relaxation or stress conditions. How virtual biophilic design affects HRV, and what research protocols are most effective in assessing these physiological effects remains unclear. This literature review clarify research protocols and outline the trends of HRV in virtual biophilic design and to propose guidelines for improving the accuracy and reliability of HRV measurements. Most of the reviewed studies found an equal trend of the increased parasympathetic activity correlating with a reduced anxiety, during exposure to specific virtual biophilic designs. Studies with insignificant HRV effects may be due to the inadequate measurement protocol. The clearer effects on HRV may be observed by limiting virtual exposure to 15 minutes, avoiding virtual sickness, maintaining consistent subject positions, incorporating paced breathing in all conditions during HRV recordings, and evaluating short-term HRV measures for a minimum of 5 minutes. Virtual biophilic exposure holds promise for pre-construction design assessment, depending on appropriate methodologies.